Review of Existing Brace Adherence Monitoring Methods to Assess Adherence. Issue 4 (October 2016) - Thatipelli, Sneha; Arun, Anupama; Chung, Philip; Etemadi, Mozziyar; Heller, James Alex; Kwiat, Dillon; Imamura-Ching, Jill; Harrison, Michael R.; Roy, Shuvo
ABSTRACT: Introduction: Outcomes of therapeutic orthopedic brace treatments are highly dependent on adherence. Medical brace adherence studies over several years have noted the poor adherence rates among many orthopedic and orthodontic medical braces. Lack of adherence has been demonstrated in many studies to lead to unsatisfactory results. With decreased adherence, desired therapeutic effects are difficult, if not impossible to achieve, regardless of the ability of the clinical intervention. Nonadherence also burdens the health care system with preventable costs due to disease progression and the necessity for increased intervention. The problem is also compounded by the inability to reliably measure adherence rates among brace wearers. In addition, no current review of the adherence monitoring systems used in orthotic braces exists. Materials and Methods: Searches were conducted on PubMed and Cochrane databases using the following terms individually or in combination: adherence, compliance, remote monitoring, brace treatment, scoliosis, mini magnetic mover 3MP, Pectus Excavatum, fitness trackers, activity trackers, FitBit, JawBone, and Nike FuelBand . In addition, references found in these articles were reviewed and used if applicable. The goal was to assess brace adherence monitoring platforms across different age groups and disease states. Because many of the modalities used to quantify adherence arose after the year 2000, we focused on this year range due to availability of better sensors and data validation. From this method, articles on adherence rates and monitoring systems in scoliosis, clubfoot, ankle, and knee immobilizer bracings were reviewed to analyze the low adherence. Commercial fitness trackers were assessed for their ability to monitor daily fitness metrics and use goal setting as a way to bolster adherence in relation to medical brace monitoring. Results: Adherence among all medical braces is remarkably low, leading to further disease progression and increased interventions and health expenditures. Orthodontic headgear has adherence rates at 56.7%. Clubfoot braces have a nonadherence rate ranging from 30% to 41%. Scoliosis braces have similar nonadherence rates ranging from 27% to 45%. In one study, a third of scoliosis patients only wore their brace for less than 2 hrs/d, and of this group, 44% of them needed surgical measures for spinal correction. However, much of these data comes from self-reported adherence. Studies comparing sensor-based and self-reported adherence highlighted a possible discrepancy between the two. In clubfoot bracing, the adherence data for the first 3 months were statistically different between the pressure-based sensor and the self-reported values ( P < 0.0001). An analysis on scoliosis bracing adherence showed that there was no statistically significant discrepancy ( P = 0.000) between self-reported and sensor-based adherence. This disconnect indicates that patients and caregivers may not be reliable historians. All the adherence tracking systems in these articles required data downloads at clinic visits, and none used real-time monitoring for adherence measurement. Moreover, when individuals knew they were being monitored for adherence, their wear rate with scoliosis bracing increased (85.7% vs. 56.5%, P = 0.029). Fitness trackers have also been shown to be able to increase amount of physical activity by 4.3 min/wk and number of daily steps by 800 to 1266 steps/d through self-monitoring and engagement strategies. The combination of real-time tracking with patient goal setting can create a platform for clinicians to intervene earlier and may have a role in improving adherence. Conclusions: Real-time monitoring is the next direction for medical device adherence. It can help close the gap between self-reported and actual adherence data, while facilitating a more therapeutic outcome with the ability to intervene with earlier health interventions from the care team. Because we currently do not have a robust system in place to quantify adherence, a real-time monitoring platform can pave the way as a method to help gather accurate adherence data and help validate new medical braces entering the field of orthotics. An approach of remote adherence monitoring system can be applied to brace systems as a platform for an early intervention in case of nonadherence and provide real-time monitoring data accessible to both patient and physician for individualized goal setting, possibly facilitating an increase in adherence.